2009
DOI: 10.1200/jco.2009.27.18_suppl.lba4009
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of chemoradiation using mitomycin or cisplatin, with or without maintenance cisplatin/5FU in squamous cell carcinoma of the anus (ACT II)

Abstract: LBA4009 Background: Chemoradiotherapy (CRT) with 5-fluorouracil (5-FU) and mitomycin-C (MMC) is standard treatment for anal cancer. This trial addresses two questions: whether (i) replacing MMC with cisplatin (CDDP) improves the complete response (CR) rate, and (ii) two cycles of maintenance chemotherapy after CRT reduces recurrence. Methods: Between 2001 and 2008, 940 patients (pts) were recruited to a multicenter, randomized factorial trial. Pts received 5-FU (1,000mg/m2/day on d1–4 and 29–32), radiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 0 publications
4
48
0
3
Order By: Relevance
“…Leukocytes encompass all WBCs, including lymphocytes, and lymphopenia is a known side effect of radiation of pelvic bone marrow. Significant leukopenia and neutropenia are side effects of MMC, as established by numerous trials of anal cancer patients [15,16]. Our data further corroborate the impact of MMC on the WBC count, as the number of MMC cycles was a predictor of both Grade 2 + leukopenia and neutropenia.…”
Section: Discussionsupporting
confidence: 88%
“…Leukocytes encompass all WBCs, including lymphocytes, and lymphopenia is a known side effect of radiation of pelvic bone marrow. Significant leukopenia and neutropenia are side effects of MMC, as established by numerous trials of anal cancer patients [15,16]. Our data further corroborate the impact of MMC on the WBC count, as the number of MMC cycles was a predictor of both Grade 2 + leukopenia and neutropenia.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the authors of the ACT II trial conclude that MMC-based therapy should remain the standard-of-care, despite the fact that both regimens had similar recurrence-free survival and overall survival. (12)…”
Section: Discussionmentioning
confidence: 99%
“…There was significantly higher hematologic toxicities with the use of MMC (25% vs. 13%; p < 0.001). (12) Unfortunately, the second randomization of two additional courses of cisplatin/5FU maintenance chemotherapy after completion of primary chemoradiation makes answering the question of primary chemoradiation using cisplatin/FU vs. MMC/FU in the primary treatment of anal cancer more difficult. Although we would agree with the authors conclusion that 5-FU/MMC without maintenance remains the standard of care for the management of anal cancer, given the more favorable side effect profile, cisplatin based chemoradiation regimens should still be considered as an alternative chemotherapy backbone on which to add biologics in clinical trials that seek to improve the local control results of patients with anal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, colostomy rates (cumulative rate 19 versus 10 percent; P = .02) were significantly higher in the induction cisplatin/5-FU arm [21]. The ACT II study on the other hand showed no difference between mitomycin-C or cisplatin containing regimens in any of the above parameters including colostomy rates [22]. …”
Section: Discussionmentioning
confidence: 99%